DETEKSI FRAUDULENT FINANCIAL STATEMENT: PENGUJIAN DENGAN ANALISIS PROKSI FRAUD TRIANGLE - Made Irma Lestari; Vosby Florensi (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2022)
This study is an empirical study that aims to determine the effect of the fraud triangle proxies on the potential on fraudulent financial statements of go-public companies on the Indonesia Stock Exchange. This study uses 22 companies that are members of the LQ-45 company for the 2016-2020 period. The test results with multiple linear regression showed that simultaneously financial targets, financial stability, external pressure, nature of industry, and change in auditors had a significant positive effect on fraudulent financial statements. Partially, the Pressure Factor with the Financial Stability proxy has a significant positive influence on the potential for financial statement fraud. However, the results of the simultaneous test of proxies for pressure factors, namely financial target, financial stability, and external pressure, did not have a significant effect. The partial test results on each variable state that the other hypotheses, namely financial targets, external pressure, nature of industry, and change in auditors, do not have a significant positive effect on potential fraud in financial statements. Keywords: Fraudulent financial statement, pressure, opportunity, rationalization.